2022
DOI: 10.1109/ojies.2022.3149093
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Orchestration and Configuration Services in Industrial IoT Systems: An Autonomic Approach

Abstract: Research leading to these results has received funding from the EU ECSEL Joint Undertaking under grant agreement n • 737459 (Productive4.0 project) and n • 826452 (Arrowhead Tools project), and from the Research Council of Norway (project n • 282904).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this recommendation, the key focus is on integrating network components such as IoT gateways, routers, and switches into existing control systems. This integration facilitates the transmission of data from IoT devices to a central system or the cloud, enabling remote monitoring and basic data analytics [76]. The core idea behind this recommendation is to enhance existing control systems with IIoT devices, empowering them to adapt operations in real time based on incoming data.…”
Section: (B) Level One-add Communication Using Iiot Devices To Existi...mentioning
confidence: 99%
“…In this recommendation, the key focus is on integrating network components such as IoT gateways, routers, and switches into existing control systems. This integration facilitates the transmission of data from IoT devices to a central system or the cloud, enabling remote monitoring and basic data analytics [76]. The core idea behind this recommendation is to enhance existing control systems with IIoT devices, empowering them to adapt operations in real time based on incoming data.…”
Section: (B) Level One-add Communication Using Iiot Devices To Existi...mentioning
confidence: 99%
“…The authors have showed the novelty and effectiveness of the proposed system as compare to traditional scheme. Lam et al [24] have proposed a decentralized automatic orchestration and configuration mechanism based upon semantic policies. The proposed approach was deployed and verified while sending the information during planning and production in IIoT environment while transmitting over cloud.…”
Section: Related Workmentioning
confidence: 99%